Comparison of Renal Tubular Damage with Kidney Injury Molecule-1 in Open and Laparoscopic Colorectal Cancer Surgery - Abdullah Gürhan Duyan; Celalettin Vatansev; Rahim Kocabaş; Melek Yalçın Koç; Muhammed Ali Akbulut (Medicina)
Background and Objectives: Colorectal cancer is the third most common type of cancer in men and women. With advancements in technology, minimally invasive treatment options have become increasingly prominent in colorectal cancer surgery. This study aimed to compare the increased intra-abdominal pressure in laparoscopic colon and rectal surgery with open procedures using kidney injury molecule-1 (KIM-1) secreted from renal tubules. Materials and Methods: We enrolled 46 patients diagnosed with colon cancer who underwent laparoscopic and open surgical procedures at our clinic. The patients were prospectively randomized into five groups: 10 laparoscopic right hemicolectomies (Group 1), 8 open right hemicolectomies (Group 2), 8 laparoscopic anterior resections (LARs) (Group 3), 11 open anterior resections (Group 4), and 9 laparoscopic low anterior resections (Group 5). Urine samples were collected from the patients preoperatively, postoperatively at the 4th hour, and postoperatively on the 14th day, and the urine KIM-1 levels and urine creatinine (Cr) values were measured. The urine KIM-1/Cr ratios were subsequently calculated. Results: The urinary KIM-1/Cr levels increased at the 4th postoperative hour after the open and laparoscopic procedures. On postoperative day 14, the urinary KIM-1/Cr levels were lower than those in the preoperative period in all groups, except the LAR group. Conclusions: Our study shown that the average pressure in laparoscopic colon and rectal surgery did not have a long-term impact on kidney injury in comparison to open colon and rectal surgery.